2020
DOI: 10.1177/1362361320965397
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Autism Observation Scale for Infants with community-ascertained infants showing early signs of autism

Abstract: Often included within ‘high-risk sibling’ studies, the Autism Observation Scale for Infants (AOSI) has only one independent replication study and no evaluation with community-ascertained cohorts. We administered the AOSI and established clinical measures with 103 infants (68% male) at ‘high autism likelihood’ on the Social Attention and Communication Surveillance - Revised (SACS-R) tool, at 9–14 months of age and again 6 months later. AOSI Total scores showed adequate internal consistency and strong inter-rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Although the present study aimed to investigate the natural course of motor difficulties and its predictive association with emergent signs of ASD, it is unlikely that all infants identified at moderate‐to‐high concern in our sample will receive an ASD diagnosis. This has been discussed in a previous paper using data from this cohort (Hudry et al, 2020). This has also been highlighted in previous longitudinal infant studies, such as through the Baby Siblings Research Consortium (BSRC), which reported that 42% of high risk infants presenting with an elevated 36‐month ADOS score did not meet formal diagnostic criteria (Iverson et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Although the present study aimed to investigate the natural course of motor difficulties and its predictive association with emergent signs of ASD, it is unlikely that all infants identified at moderate‐to‐high concern in our sample will receive an ASD diagnosis. This has been discussed in a previous paper using data from this cohort (Hudry et al, 2020). This has also been highlighted in previous longitudinal infant studies, such as through the Baby Siblings Research Consortium (BSRC), which reported that 42% of high risk infants presenting with an elevated 36‐month ADOS score did not meet formal diagnostic criteria (Iverson et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…These differences may have contributed to the low agreement in CBE ratings across sessions. Together, the modest stability in scores and variability in specific items underscore the need for multiple assessments and routine developmental surveillance, as has been previously articulated (Hudry et al, 2021;Wieckowski et al, 2021). There are several limitations to this study that should be acknowledged.…”
Section: Discussionmentioning
confidence: 81%
“…Early detection tools for Autism Spectrum Disorder (ASD) are typically comprised of items capable of detecting social communication (Janvier et al, 2019;Roy, 2019;Lee et al, 2019;Hudry et al, 2021 andZwaigenbaum et al, 2021;Wetherby et al, 2021;Wu et al, 2020;Pandolfi, Magyar, & Dill, 2017;Hudry et al, 2021;Choueiri et al, 2021). Several other instruments detect them by exploiting behavioral issues (Janvier et al, 2019;Rescorla et al, 2019;Coulter et al, 2021;Roman-Urrestarazu et al, 2021;Razaet al, 2019;Pandolfi, Magyar, & Dill, 2017;Hudry et al, 2021;Au et al, 2020). Meanwhile, emotional problems (Rescorla et al, 2019), sensory regulatory problems (Lee et al, 2019), and engagement problems (Hudry et al, 2021) can also be used for the early detection of children with Autism Spectrum Disorder.…”
Section: Research Findingsmentioning
confidence: 99%
“…Several other instruments detect them by exploiting behavioral issues (Janvier et al, 2019;Rescorla et al, 2019;Coulter et al, 2021;Roman-Urrestarazu et al, 2021;Razaet al, 2019;Pandolfi, Magyar, & Dill, 2017;Hudry et al, 2021;Au et al, 2020). Meanwhile, emotional problems (Rescorla et al, 2019), sensory regulatory problems (Lee et al, 2019), and engagement problems (Hudry et al, 2021) can also be used for the early detection of children with Autism Spectrum Disorder. Further explanation can be seen in Table 1.…”
Section: Research Findingsmentioning
confidence: 99%